Development of a combination of noradrenergic and antimuscarinic drugs for the treatment of obstructive sleep apnea: Challenges and progress - Taranto-Montemurro, Luigi; Pho, Huy; White, David P. (Frontiers in Sleep, 2023)
Obstructive sleep apnea (OSA) is a disorder characterized by repetitive collapse of the upper airway during sleep, leading to intermittent hypoxia and sleep fragmentation. The combination of noradrenergic and antimuscarinic drugs has emerged as a potential pharmacological treatment option for OSA, with the most promising combination being atomoxetine plus aroxybutynin. This combination is currently undergoing extensive experimentation and will be soon tested in phase 3 studies. Other noradrenergic drugs including reboxetine, and other antimuscarinics including fesoterodine, hyoscine butylbromide, solifenacin, and biperiden have been tested. The increasing interest in OSA pharmacotherapy is driven by advances in our understanding of the pathophysiology of the disease and accumulating evidence of the surprising effectiveness of this drug combination. However, challenges remain in accurately measuring the severity of OSA, which can impact our ability to fully understand the efficacy of these medications. Further research is ongoing to address these challenges and to optimize the use of noradrenergic and antimuscarinic drugs for the treatment of OSA.